Les interventions japonaises au jardin Albert-Kahn dans la deuxième moitié du xxe siècle : vitrine et laboratoire de nouvelles conceptions du jardin japonais - Hiromi Matsugi (Projets de Paysage)
This article looks at two Japanese additions to the Albert-Kahn Japanese Garden in Boulogne-Billancourt during the second half of the 20th century. The gardener Iwatani Kōzō created a tea garden on this site in 1965, and the landscape agency Takano Landscape Planning designed a contemporary Japanese garden there in the 1980s. We examine their design work using archival documents and interviews to analyse their professional motivations and convictions within a wider cultural context. This approach seeks to highlight the diversity of views regarding what a Japanese garden should be and the dual role played by the garden as both a test ground and a showcase for these ideas. The article thus attempts to qualify the current image of this garden, which is exclusively linked to its founder at the beginning of the 20th century. It also considers this garden as a work of landscape architecture evolving over time under various influences and interpretations coming from Japan, and inspired by cultural references that are inextricably linked to historical periods.